2018
DOI: 10.1177/1071100718816292
|View full text |Cite
|
Sign up to set email alerts
|

Microvasculature of the Plantar Plate Using Nano–Computed Tomography

Abstract: Background: Lesser toe plantar plate attenuation or disruption is being increasingly implicated in a variety of common clinical conditions. A multitude of surgical techniques and devices have been recently developed to facilitate surgical repair of the plantar plate. However, the microvascular anatomy, and therefore the healing potential in large part, has not been defined. We investigated the microvasculature of the plantar plate by employing a novel technique involving microvascular perfusion and nano–comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 41 publications
0
23
0
1
Order By: Relevance
“…The detailed geometry and functionality of the vascular tree can be assessed with various imaging techniques. The most commonly used techniques are magnetic resonance imaging (MRI) and nano-CT/micro-CT, complemented with an infusion of contrast agents or fluorescent lipids to evaluate the state of perfusability [ 1 , 3 , 150 ]. See Figure 11 for an illustration of micro-CT imaging.…”
Section: Monitoring and Evaluation Of Functionalitymentioning
confidence: 99%
“…The detailed geometry and functionality of the vascular tree can be assessed with various imaging techniques. The most commonly used techniques are magnetic resonance imaging (MRI) and nano-CT/micro-CT, complemented with an infusion of contrast agents or fluorescent lipids to evaluate the state of perfusability [ 1 , 3 , 150 ]. See Figure 11 for an illustration of micro-CT imaging.…”
Section: Monitoring and Evaluation Of Functionalitymentioning
confidence: 99%
“…Більшість авторів вважають, що дегенеративні зміни ПП капсули ПФС, які виникають під впливом тривалого циклічного перевантаження, є основною причиною больового синдрому та розвитку метатарзалгії, а аваскулярність центральної частини ПП сповільнює її регенерацію в разі хронічного перевантаження [4,5,10,11].…”
Section: вступunclassified
“…7,40 Specifically, an underlying pathologic instability of the plantar plate and MTP joint collateral ligaments is seen in common clinical conditions including hammertoes and crossover toes. 16,19 These conditions represent a major source of pain and dysfunction and constitute some of the most common complaints presented to foot and ankle surgeons. 16,38 The anatomy and histochemistry of the plantar plate has been previously described, 12,18,22,25,45 drawing comparisons to the meniscus of the knee as both are fibrocartilaginous structures that sustain compressive and tensile loads.…”
Section: Introductionmentioning
confidence: 99%
“…3 A recent study has similarly demonstrated that the microvasculature of the normal plantar plate is densest at the proximal and distal attachments with a relatively hypovascular midsubstance. 19 As a tissue's potential for healing is directly linked to the availability of arterial blood supply, 4 meniscal repair is not attempted in the central zone where inflammatory and nutritional support are unavailable. 19 In contrast, there is a body of literature emphasizing the technical aspects of direct anatomic repairs of the plantar plate, yet it remains unknown whether the plantar plate has the biological capacity to heal these repairs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation